Association of the oxidative balance score with sarcopenia among young and middle-aged adults: findings from NHANES 2011–2018 - Cai, Zhi; Dong, Dantong (Frontiers in Nutrition, 2024)
Background Sarcopenia is associated with oxidative stress. The Oxidative Balance Score (OBS) is commonly used to assess dietary and lifestyle exposure to oxidative stress. However, few studies in the literature have assessed the correlation between sarcopenia and OBS. Aim This study aimed to assess the association between OBS and sarcopenia among young and middle-aged adults in the United States using data from the National Health and Nutrition Examination Survey (NHANES). Method Weighted logistic regression analysis was used to investigate the association between OBS and sarcopenia based on data from NHANES 2011–2018. Subgroup analyses were performed to observe the consistency of the outcomes, and the stability of the results was tested using sensitivity analyses. Result The final sample included 5,525 young and middle-aged American adults. A higher OBS was associated with a lower risk of sarcopenia. In the fully adjusted model, the second (odds ratio [OR]: 0.62, 95% confidence interval [CI]: 0.41, 0.94; p = 0.023), third (OR: 0.50; 95% CI: 0.34, 0.74; p < 0.001), and highest quartiles (OR: 0.18; 95% CI: 0.11, 0.28; p < 0.001) of the OBS were associated with higher risks of sarcopenia when compared to the lowest quartile. This association was consistent across both dietary and lifestyle OBS scores. Our subgroup analysis revealed no significant differences between the subgroups of variables included in the interaction analysis. Sensitivity analyses revealed similar results. Conclusion Our study showed that higher antioxidant and lower antioxidant exposure may decrease the risk of developing sarcopenia. Higher OBS scores may indicate greater protection against sarcopenia; however, further clinical studies are warranted to confirm these findings.